India says "no" to nationalisation : an analysis of public reaction to the current proposal affecting certain key sector industries - Lala, R. M. (Rajaji Foundation, 1979)
On the current proposal for nationalisation of steel, aluminium, and the automobile industries; edited from clippings preserved in the Rajaji Foundation.